How relationship marketing transforms the positioning of pharmaceutical laboratories in the healthcare market - Valderrama Puscan, Marlon Walter; Bonifaz Bolivar, Tatiana Elizabeth; Ventura Aguilar, Henry Elder (LACCEI, 2025)
The present research aimed to establish the correlation between relationship marketing and the positioning of a Trujillo 2024 pharmaceutical laboratory. The study contributes to the fulfillment of SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation and Infrastructure). The methodology was applied with a quantitative approach, non-experimental, correlational and cross- sectional design. The population consisted of 90 people, including clients and healthcare professionals, using a census sample. The collection technique was a survey using structured questionnaires, validated by expert judgment with a Cronbach’s alpha reliability of 0.767. The results showed that 83.3% of participants perceived a high level of relationship marketing, while 72.2% rated the laboratory’s positioning as high. Correlational analysis using Spearman’s Rho determined a significant positive correlation of 0.280 (p < 0.05) between the main variables. Specifically, a correlation of 0.345 (p < 0.001) was found between loyalty and positioning, 0.345 (p < 0.001) between personalized communication and positioning, and 0.280 (p < 0.008) between after-sales service and positioning. It was concluded that relationship marketing strategies effectively contribute to strengthening positioning in the local market, confirming the hypothesis and providing empirical evidence on the importance of relationship strategies.